Subject’ and ‘Objectivity’ in the Theory of Historiography - Horský, Jan (Dějiny – teorie – kritika, 2015)
In his polemic text, which reacts to a study by Mikuláš Čtvrtník, the author draws attention to the currently usually unreflected use of the terms subjective and objective in historical, anthropological, and sociological texts. This theoretical contribution focuses on the subject of the researcher and on subjectivity as a way of perceiving social reality in the cognitive process.